2013
DOI: 10.1590/s1519-69842013000400013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of peak flow changes on the macroinvertebrate drift downstream of a Brazilian hydroelectric dam

Abstract: Successive daily peak flows from hydropower plants can disrupt aquatic ecosystems and alter the composition and structure of macroinvertebrates downstream. We evaluated the influence of peak flow changes on macroinvertebrate drift downstream of a hydroelectric plant as a basis for determining ecological flows that might reduce the disturbance of aquatic biota. The aim of this study was to assess the influence of flow fluctuations on the seasonal and daily drift patterns of macroinvertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 38 publications
3
16
0
1
Order By: Relevance
“…Drift is usually greatest when large masses of water are present, which is typical in spring (or at least more common than in summer) (Brittain and Eikeland, 1988;Principe and del Carmen Corigliano, 2006;Baryshev and Veselov, 2007). The dependence of drift on changes in water flow was also demonstrated previously, in analyses of drift in anthropogenic conditions (Castro et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Drift is usually greatest when large masses of water are present, which is typical in spring (or at least more common than in summer) (Brittain and Eikeland, 1988;Principe and del Carmen Corigliano, 2006;Baryshev and Veselov, 2007). The dependence of drift on changes in water flow was also demonstrated previously, in analyses of drift in anthropogenic conditions (Castro et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…Further, we were surprised by high treatment effects of Hydropsychidae , due to its association to the interstices in fast flowing river sections (Petersen, ; Schuhmacher, ). Yet other studies reported correspondingly strong drift responses (Castro et al, ; Gibbins, Vericat, & Batalla, ) as well as reduced abundances in hydropeaking affected river stretches (Céréghino et al, ; De Jalon, Sanchez, & Camargo, ; Novotny, ).…”
Section: Discussionmentioning
confidence: 92%
“…However, in the tropical zones, most of the studies concentrate on the temporal variability of the aquatic communities as a function of the season in the year (Jacobsen & Encalada, ; Mesa, ; Ríos‐Touma et al, ) without considering flood and drought discharge (i.e., hydrological) thresholds and their impact on aquatic communities. Exceptions hereon are the studies in altered rivers of Castro, Hughes, and Callisto (), Miserendino (), and Herrera and Burneo () that examined the response of macroinvertebrates and Lima et al () and García, Jorde, Habit, Caamaño, and Parra () of fish.…”
Section: Introductionmentioning
confidence: 99%